Energy Saving in Pilger Mill Electric Drives Complete Solution - Yuriy Usynin; Dmitry Sychev; Nikita Savosteenko (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
This paper considers issues related to increasing energy efficiency in electric drives of pilger rolling mills, presenting kinematics of such mills, provides justification for the general load chart, presents the detailed review of reference materials on technical energy saving solutions, and suggests a math model of an electric drive with a field regulated reluctance machine. The paper suggests key methods of saving energy in electric drives of pilger mills, namely: kinematic scheme improvement; main energy drainers and ways of energy loss reduction in electric drives with direct- and alternate-current motors, energy-saving electric drive control profiles. The article compares energy-saving resources in electric drives with various-type motors (direct-current motors, synchronous motors, and field regulated reluctance machine), clarifies the scheme of energy-saving resource implementation, provides the qualitative evaluation of electric drive control method efficiency. The accent is made on high energy efficiency of the proportionate control of armature and excitation circuits and across the range of torque in electric drives of abruptly-variable-load mills. The highest economic effect is reached in the electric drive with a field regulated reluctance machine – by means of implementing the energy-efficient electromechanical converter and applying energy-saving control profiles.